(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Laparoscopic sleeve resection of the stomach remains one of the leading methods of surgical treatment of morbid obesity, however, the optimal technique of intervention — classical or enhanced (Hard) — remains a subject of debate. The study included 785 patients who underwent laparoscopic gastric sleeve resection followed by 36 months of follow-up. The classical technique of laparoscopic sleeve resection of the stomach, implemented using a 36 Fr caliber and moderate mobilization of the fundus of the stomach, is a widely tested and anatomically gentle technique. In the course of the present study, it was performed on 372 patients and showed a consistently low level of postoperative complications. The rate of early surgical complications was only 1.34%, while in the Hard group it was 2.41%. Suture failure, stenoses, and fistulas were almost nonexistent, due to lower intragastric pressure and preservation of the physiological parameters of the tube. Early metabolic disorders were also reported much less frequently: hypovolemia - 18.23%, metabolic acidosis - 14.75%, hypercoagulation - 2.41%, indicating a milder physiological response to the intervention.